Development of an Instructional Video on Nail extension Using Nail tips with the Rubber base Technique for Eleventh-Grade Beauty Program Students at SMKN 3 Bogor - Dinda Varazena Melia; Nurul Hidayah; Aniesa Puspa Arum (Yayasan Vifada Cendikia Indonesia, 2026)
This study aimed to develop an instructional video on nail extension using nail tips with the rubber base technique that is valid, practical, and effective in improving the knowledge of eleventh-grade Beauty Program students at SMKN 3 Bogor. The study was motivated by the limited learning media available for the nail extension topic, which made it difficult for students to understand the practical procedures in detail, particularly during classroom demonstrations. This study employed the Research and Development (R&D) method using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The product developed was an instructional video containing theoretical materials and a step-by-step demonstration of the nail extension procedure using nail tips with the rubber base technique. The product's validity was evaluated by subject matter experts and a media expert, followed by practicality and effectiveness testing involving students. The results showed that the first subject matter expert's validation score increased from 50% to 96%, while the second subject matter expert's score improved from 60% to 100%, both of which were categorized as highly valid. The media expert's validation score also increased from 88% to 94.67%, which was categorized as highly valid. The one-to-one evaluation obtained a score of 87.69%, indicating that the product was highly feasible. The practicality test results indicated that the instructional video was highly practical, with percentages of 90.89% in the small-group trial and the field test using the effectiveness test showed an increase in student knowledge, indicated by an average pre-test score of 60.44 which increased to 95.97 in the post-test, with an N-Gain score of 0.90 falling into the high category. Based on these findings, it can be concluded that the developed instructional video is valid, practical, and effective for use as a learning medium for teaching nail extension to eleventh-grade Beauty Program students at SMKN 3 Bogor.